Rural development program in tribal region: A protocol for adaptation and addressing climate change vulnerability. (April 2017) - Jha, Shashidhar Kumar; Mishra, Sameera; Sinha, Bhaskar; Alatalo, Juha M.; Pandey, Rajiv
Abstract: Tribal peoples globally are among the most vulnerable groups to climate change and variability. This is due to a combination of their relative poverty and their dependence on agriculture and natural support systems (NSS). Hence programmes that simultaneously help to reduce poverty and vulnerability to climate change are needed. The Indian Government has launched the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), an incentive-based programme addressing vulnerability to poverty, climate change and NSS by integrating natural systems (water, land, soil) and human systems (employment opportunities). Here we show that the vulnerability related to climate variability, agriculture, water and household economic conditions has decreased significantly due to MGNREGA interventions. Specifically, water availability, diversification of agriculture, crop yield and income have all increased. Besides the decreased vulnerability to climate change due to better access to water, the intervention has also increased employment opportunities and daily wage levels have almost doubled, thus improving the economic status of tribal peoples. These changes have led to improved living conditions, facilitating better adaptation to both natural and economic stresses. This case study illustrates the potential of well-designed government programmes to contribute to sustainable development through improving adaptive capacity and by combating poverty and vulnerability to climate change among marginalised people. Highlights: Tribal peoples globally are among the most vulnerable groups to climate change. Programmes that reduce poverty and vulnerability to climate change are needed. India has launched programme addressing vulnerability to poverty and climate change. Vulnerability to climate variability economic conditions decreased significantly.